Environmental exposure of arsenic and fluoride and their combined toxicity: A recent update. Issue 5 (22nd December 2019) - Mondal, Paritosh; Chattopadhyay, Ansuman
Abstract: Environmental exposure to arsenic (As) and fluoride (F) in the recent year has been increased because of excessive use of naturally contaminated ground water. Surface water is also regularly contaminated with these elements in various industrial areas. Arsenicosis and fluorosis upon individual exposure of As and F are reported in many studies. A syndrome of endemic As poisoning and fluorosis occurs during concurrent exposure of As and F. Previous reports showed synergistic, antagonistic and independent effects of these two compounds, although few recent reports also revealed antagonistic effects after co‐exposure. Interaction during intestinal absorption and influence of F on As metabolism might be the cause of antagonism. The synergism/antagonism is thought to depend on the dose and duration of the co‐exposure. However, the detailed mechanism is still not fully understood and needs further studies. Removal technologies of As and F from contaminated water is available but removal of such contaminants from food is yet to be developed. Antioxidants are useful to mitigate the toxic effects of As and F. This review focused on the effect of co‐exposure, amelioration as well as removal techniques of As and F. Abstract : Several parts of the world are facing serious problems due to detrimental effects of arsenic (As) and fluoride (F). Mixture effects of As and F have shown ambiguity based on dose of exposure, duration of exposure and types of model organism. Use of ameliorative agents and removal techniques are the best options of obtaining relief from such toxicity.